2017
DOI: 10.3892/etm.2017.5181
|View full text |Cite
|
Sign up to set email alerts
|

Insect tea attenuates hydrochloric acid and ethanol‑induced mice acute gastric injury

Abstract: Abstract. The aim of the present study was to investigate the protective effect of insect tea on HCl/ethanol-induced gastric ulcers in ICR mice. The serum levels of vasoactive intestinal peptide, substance P, somatostatin, motilin and endothelin-1 in mice were assessed using commercial kits and gastric tissues of superoxide dismutase (SOD, nitric oxide (NO) and malondialdehyde (MDA) were determined using western blot analysis Insect tea significantly reduced HCl/ethanol-induced gastric juice secretion and incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…Our results showed that the expression of EGF and EGFR in the gastric tissue of HCl/ethanol-induced gastric injury mice was significantly lower than that of normal mice. EGF, as a protective factor, combines with its receptor EGFR to accelerate ulcer healing, increase tissue repair ability, and maintain ulcer healing quality [46,47]. In the current study, the treatment of HFY09 significantly increased the expression level of EGF and EGFR genes in the gastric tissue of mice with gastric injury, indicating that HFY09 has a protective effect on the gastric tissue of mice with gastric injury, and the effect is stronger at a higher dose.…”
Section: Discussionsupporting
confidence: 53%
“…Our results showed that the expression of EGF and EGFR in the gastric tissue of HCl/ethanol-induced gastric injury mice was significantly lower than that of normal mice. EGF, as a protective factor, combines with its receptor EGFR to accelerate ulcer healing, increase tissue repair ability, and maintain ulcer healing quality [46,47]. In the current study, the treatment of HFY09 significantly increased the expression level of EGF and EGFR genes in the gastric tissue of mice with gastric injury, indicating that HFY09 has a protective effect on the gastric tissue of mice with gastric injury, and the effect is stronger at a higher dose.…”
Section: Discussionsupporting
confidence: 53%
“…Nitric oxide, derived from constitutive nitric oxide synthase, is a vital endogenous mediator of mucosal defense and plays a significant role in the maintenance of normal gastric mucosal integrity [54]. This role of NO may be due to its ability to reduce neutrophil infiltration [55] and to influence blood flow in gastric tissues during the healing process of gastric ulcer [56]. In the present study, ethanol ulcerated group showed significant reduction in gastric NO levels in comparing to control group.…”
Section: Discussionmentioning
confidence: 99%
“…The hepatocytes were then sonicated by SJIALAB for 2 min (10% ultrasound intensity), and centrifuged (4500 rpm) for 10 min to separate the supernatant. The extracted protein was then subjected to polyacrylamide gel electrophoresis (80–120 V), and transferred onto a polyvinylidene fluoride (PVDF) membrane, sealed, and incubated overnight at 4 °C with the corresponding primary antibodies, namely, cyclooxygenase 2 (COX-2; MA514568, Thermo Fisher Scientific), inducible nitric oxide synthase (iNOS) (PA1036), NF-κB (PA1186), phosphorylated (p)-NF-κB p65 (MA515160), nuclear factor of κ-light polypeptide gene enhancer in B-cells inhibitor-α (IκB-α; 397700), Cu/Zn-SOD (PA5270240), Mn-SOD (PA530604), GSH-Px (PA540504), CAT (PA259183), cytochrome P450 reductase (PA577820), and β-actin (MA5157739), incubated at 37 °C with the second antibody (A21241) for 1 h, followed by colorimetric detection and chemiluminescence imaging (iBright FL1000, Thermo Fisher Scientific) [ 23 ].…”
Section: Methodsmentioning
confidence: 99%